Сlassification of three-digit elementary functions for cryptographic transformation of the information - БАБЕНКО, Віра Григорівна; МЕЛЬНИК, Ольга Григорівна; МЕЛЬНИК, Руслан Павлович (Ukrainian Scientific Journal of Information Security, 2013)
In the article presents the three-digit classification of elementary functions for cryptographic transformation of the information depending on the complexity of the elementary functions and the method of converting information elementary functions of each group.